Fitness Related to Depression and Quality of Life in Older People - Sáez-Padilla, Jesús; Sierra-Robles, Ángela; Tornero-Quiñones, Inmaculada; Espina-Díaz, Alejandro; Carvajal-Duque, Pedro (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
This research aimed to concretize the relationship between physical fitness with depression and quality of life in the sedentary and non-sedentary older people of the social centres of the City of Huelva. We have measured the variables: Physical Fitness (Senior Fitness Test), depression (Geriatric Depression Scale) and quality of life (SF36). We evaluated 63 sedentary older people between 60 and 87 years old (M = 71.2; SD = 5.81) and 66 non-sedentary older people between 60 and 87 years old (M= 69.71; DS=6.1). By gender, in sedentary older people 22.2% were men (n = 14) and 77.8% women (n = 49) and in non-sedentary 19.7 % were men (n=13) and 80.3% women (n=53). The physical fitness of the sedentary majors is some points above the non-sedentary ones, except the values of strength. In terms of depression, women have a higher depressive state than men and with higher values in sedentary versus non-sedentary. Finally, regarding the relationship between fitness level and depression, there is a positive relationship, especially an optimal level of strength favours a lower depression. The conclusions of the study emphasized that the physical fitness of the sedentary majors is above the non-sedentary ones, except the values of strength. In terms of depression, women have a higher depressive state than men and with higher values in sedentary versus non-sedentary.